Analysis of the effect of explosion grounding electrode on grounding resistance reduction. Issue 16 (13th February 2019) - Wang, Yongli; Wang, Sen; Zhang, Jian; Li, Zhizhong; Xu, Li
Abstract : Developing cracks in the soil by means of explosions in the holes, as is called the explosion grounding electrode in this study, is a very effective way to reduce the grounding resistance in the area with high resistivity soil. In this study, the influence of the grounding grid scale and the arrangement of the grounding electrode on reducing the grounding resistance of three‐dimensional grounding grid with explosion grounding electrode are studied. There is a strong shielding effect between the explosion grounding electrodes. When the distance between the explosion grounding poles is short, the effectiveness of reducing the grounding resistance by using the long explosion grounding electrode is obviously restrained. The distance between the explosion grounding electrodes should be more than half the length of the electrodes.